LO47: Concussions in minor hockey players before and after implementation of a policy to limit body checking. (May 2019) - Loewen, N.; Gaudet, L.; Franczak, B.; Rowe, B.
Abstract : Introduction : Concussions are one of the most common sports-related injuries presenting to emergency departments (EDs), and are particularly frequent among players of contact sports such as ice hockey (hockey). Studies of youth hockey players report increased concussion incidence when participating in levels of hockey that allow body-checking. In 2016, an Edmonton minor hockey organization implemented a policy to remove body checking from play for non-elite levels of Bantam (13-14 years) and Midget (15-17 years). This study aimed to evaluate the effect of this policy on occurrence of concussions in male minor hockey players.Methods : Alberta Health Services Sport and Recreation codes (SR = 54) were used to identify Bantam and Midget hockey players presenting to Edmonton Zone emergency departments (ED) during the 2013/2014 to 2016/2017 hockey seasons from the National Ambulatory Care Record System. Injured hockey players with a concussion were identified using International Classification of Diseases 10-CA diagnosis code S06.0. Odds ratios (OR) of concussions among total hockey injuries before (2013-2016) and after (2016-2017) the policy are reported with 95% confidence intervals (CIs). Differences were assessed using Pearson's χ2 test.Results : During the study period, 1978 minor hockey players presented to an Edmonton Zone ED with a hockey-related injury, including 272 players with a concussion (14%). Most of the injuries occurred to Midget players (n = 1274). The proportions of concussion were similar before and after the policy change for players of all ages (OR = 0.78; 95% CI: 0.37 to 0.92) and for injured Bantam players (OR = 0.97; 95% CI: 0.59 to 1.55); however, there was a significant reduction in concussions as a proportion of all injuries for Midget players before and after the policy change (OR = 0.61; 95% CI: 0.36 to 1.00).Conclusion : In the initial year of implementation, the policy to limit body-checking to elite levels of play had mixed results. While the policy change did not result in a significant reduction in concussions overall, or for Bantam players, Midget players did experience a significant reduction in concussions after the policy change. The reasons behind these age-related differences require further investigation. Moreover, further evaluation of the policy using additional years of post-policy data, as well as hockey registration numbers, is needed to evaluate the sustainability of its effect.